2015
DOI: 10.1136/jclinpath-2015-203203
|View full text |Cite
|
Sign up to set email alerts
|

Adverse histological features in malignant colorectal polyps: a contemporary series of 239 cases

Abstract: Surgical resection should be recommended if ≥2 of these adverse histological features are present and may be warranted if one feature is present. A positive margin may require additional local resection but not necessarily surgery if no other adverse factors are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 29 publications
8
56
0
Order By: Relevance
“…These phenomena led to cribriform morphology (CM) over longer‐term culture intervals of up to 12 days . While CM is regarded as a marker of malignant transformation in human colon , this study shows early features of this morphology in normal intestinal organoids when the ezrin/NHERF1 interaction was disrupted. Hence, these data suggest that cribriform morphogenesis is a consequence of bipolar spindle misorientation but is not necessarily restricted to malignant cells.…”
Section: Discussionmentioning
confidence: 77%
“…These phenomena led to cribriform morphology (CM) over longer‐term culture intervals of up to 12 days . While CM is regarded as a marker of malignant transformation in human colon , this study shows early features of this morphology in normal intestinal organoids when the ezrin/NHERF1 interaction was disrupted. Hence, these data suggest that cribriform morphogenesis is a consequence of bipolar spindle misorientation but is not necessarily restricted to malignant cells.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, according to a T1 study of 140 surgical resection specimens, a positive margin was not associated with nodal metastasis. Also, none of the malignant polyps with carcinoma present between 0.1 and 1 mm from the margin showed residual carcinoma in these 140 surgical specimens [33]. Not surprisingly, pooled data analysis of 1900 patients with malignant polyps showed that positivity of the resection margin was significantly predictive of the presence of residual disease (OR 22; 95% CI 10.3-46.6, P < 0.0001) [34].…”
Section: Treatment Decisions After T1 Polypectomymentioning
confidence: 91%
“…With no further treatment, the risks are of luminal recurrence and progression of involved undetected mesorectal lymph nodes. Current guidelines consider carcinoma within 1 mm of the resection margin as being involved but recent evidence suggests that the risk of recurrence is highest only when tumour is present at the resection margin or within diathermized tissue (Brown et al ., ). Risk factors for lymph node involvement include extent of submucosal invasion, intramural lymphovascular invasion (LVI) and poor differentiation.…”
Section: Multidisciplinary Managementmentioning
confidence: 97%